Altered thermoregulatory responses in heart failure patients exercising in the heat. Issue 21 (15th November 2016) - Balmain, Bryce N.; Jay, Ollie; Sabapathy, Surendran; Royston, Danielle; Stewart, Glenn M.; Jayasinghe, Rohan; Morris, Norman R.
Abstract: Heart failure (HF) patients appear to exhibit impaired thermoregulatory capacity during passive heating, as evidenced by diminished vascular conductance. Although some preliminary studies have described the thermoregulatory response to passive heating in HF, responses during exercise in the heat remain to be described. Therefore, the aim of this study was to compare thermoregulatory responses in HF and controls (CON) during exercise in the heat. Ten HF (NYHA classes I–II) and eight CON were included. Core temperature ( T c ), skin temperature ( T sk ), and cutaneous vascular conductance (CVC) were assessed at rest and during 1 h of exercise at 60% of maximal oxygen uptake. Metabolic heat production ( H prod ) and the evaporative requirements for heat balance ( E req ) were also calculated. Whole‐body sweat rate was determined from pre–post nude body mass corrected for fluid intake. While H prod (HF: 3.9 ± 0.9; CON: 6.4 ± 1.5 W/kg) and E req (HF: 3.3 ± 0.9; CON: 5.6 ± 1.4 W/kg) were lower ( P < 0.01) for HF compared to CON, both groups demonstrated a similar rise in T c (HF: 0.9 ± 0.4; CON: 1.0 ± 0.3°C). Despite this similar rise in T c, T sk (HF: 1.6 ± 0.7; CON: 2.7 ± 1.2°C), and the elevation in CVC (HF: 1.4 ± 1.0; CON: 3.0 ± 1.2 au/mmHg) was lower ( P < 0.05) in HF compared to CON. Additionally, whole‐body sweat rate (HF: 0.36 ± 0.15; CON: 0.81 ± 0.39 L/h) was lower ( P = 0.02) in HF compared to CON. Patients with HF appear to be limited in their ability to manage a thermal load and distribute heat content to the body surface (i.e., skin), secondary to impaired circulation to the periphery. Abstract : The purpose of this study was to examine thermoregulatory responses and human heat balance parameters in heart failure patients compared to control participants during exercise in a warm environment. Our data show that patients with heart failure appear to be limited in their ability to manage a thermal load during exercise in a warm environment, as evidenced by disrupted human heat balance secondary to impaired circulation to the periphery.